2022
DOI: 10.2174/1389557521666211101162449
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Properties of Dietary Chrysin: A Cellular Mechanism Review

Abstract: : Diabetes mellitus is the most common chronic metabolic disorder and is considered one of the leading causes of morbidity and mortality. The improperly-treated chronic hyperglycemia of diabetes has been related to several long-term complications and multiple organ failures, including nephropathy, which can lead to kidney failure, retinopathy with the potential loss of vision, and cardiovascular symptoms. Current commercially available synthetic glucose-lowering agents have been reported to have several advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Chrysin, isolated from various plants such as the blue passion flower ( Passiflora caerulea L.), is a flavonoid compound with a variety of pharmacological activities including antidiabetic, anti-inflammatory, and antitumor activities [ 114 , 115 , 116 ]. Sa et al, reported a novel salt cocrystal of chrysin (ChrH) and berberine (BerbOH) [ 71 ], which is also a new drug−drug cocrystal based on two natural products.…”
Section: Functions Of Flavonoid Cocrystalsmentioning
confidence: 99%
“…Chrysin, isolated from various plants such as the blue passion flower ( Passiflora caerulea L.), is a flavonoid compound with a variety of pharmacological activities including antidiabetic, anti-inflammatory, and antitumor activities [ 114 , 115 , 116 ]. Sa et al, reported a novel salt cocrystal of chrysin (ChrH) and berberine (BerbOH) [ 71 ], which is also a new drug−drug cocrystal based on two natural products.…”
Section: Functions Of Flavonoid Cocrystalsmentioning
confidence: 99%
“…Baicalein is a bioactive flavonoid in the dried roots of Scutellaria baicalensis Georgi 8 . Its biological activities have been reported in previous studies, including antithrombotic, antibacterial, anti‐inflammation, antiviral, antidiabetic, and anticancer activities 9–15 . Moreover, baicalein restrained the development of various malignancies via multiple cellular signaling pathways.…”
Section: Introductionmentioning
confidence: 96%
“…8 Its biological activities have been reported in previous studies, including antithrombotic, antibacterial, anti-inflammation, antiviral, antidiabetic, and anticancer activities. [9][10][11][12][13][14][15] Moreover, baicalein restrained the development of various malignancies via multiple cellular signaling pathways. Previous studies indicated that baicalein triggered cell apoptosis and hampered cell growth in osteosarcoma through regulating the Wnt/β-catenin pathway, 16 in prostate cancer through the AKT/mTOR pathway, 17 in gastric cancer through mediating the FAK/AKT pathway, 18 and in colorectal cancer through modulating the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Chrysin (5,7-dihydroxy flavones) is a naturally-occurring flavone found in flowers, honey, mushrooms, and propolis [ 11 ]. The anxiolytic [ 12 ], antioxidant [ 13 ], antidiabetogenic [ 14 ], anti-cancer [ 15 ], and antiestrogenic [ 16 ] properties of chrysin have been reported. For example, antiaging effect of chrysin has been investigated in d-galactose-induced aging model in rats [ 13 ].…”
Section: Introductionmentioning
confidence: 99%